Dutch validation of the low anterior resection syndrome score. (16th May 2018) - Hupkens, B. J. P.; Breukink, S. O.; Olde Reuver of Briel, C.; Tanis, P. J.; de Noo, M. E.; van Duijvendijk, P.; van Westreenen, H. L.; Dekker, J. W. T.; Chen, T. Y. T.; Juul, T.
Abstract: Aim: The aim of this study was to validate the Dutch translation of the low anterior resection syndrome (LARS) score in a population of Dutch rectal cancer patients. Method: Patients who underwent surgery for rectal cancer received the LARS score questionnaire, a single quality of life (QoL) category question and the European Organization for Research and Treatment of Cancer (EORTC) QLQ‐C30 questionnaire. A subgroup of patients received the LARS score twice to assess the test–retest reliability. Results: A total of 165 patients were included in the analysis, identified in six Dutch centres. The response rate was 62.0%. The percentage of patients who reported 'major LARS' was 59.4%. There was a high proportion of patients with a perfect or moderate fit between the QoL category question and the LARS score, showing a good convergent validity. The LARS score was able to discriminate between patients with or without neoadjuvant radiotherapy ( P = 0.003), between total and partial mesorectal excision ( P = 0.008) and between age groups ( P = 0.039). There was a statistically significant association between a higher LARS score and an impaired function on the global QoL subscale and the physical, role, emotional and social functioning subscales of the EORTC QLQ‐C30 questionnaire. The test–retest reliability of the LARS score was good, with an interclass correlation coefficient of 0.79. Conclusion: The good psychometric properties of the Dutch version of the LARS score are comparable overall to the earlier validations in other countries. Therefore, the Dutch translation can be considered to be a valid tool for assessing LARS in Dutch rectal cancer patients.